PENGARUH UKURAN PERUSAHAAN, ENVIRONMENTAL SOCIAL GOVERNANCE, DAN LEVERAGE TERHADAP TAX AVOIDANCE - Rahmawati, Sitti; Nadi, Luh (Jurnal Akuntansi dan Perpajakan Jayakarta, 2025)
Taxes are contributions that must be paid by individuals or entities to the government, which are used as a source of state income to support the community's economy. Indonesia, with its large population and wealth of resources, is the center of world trade. Taxes function as a source of state income to meet public needs and finance the state budget (APBN). Taxes not only function as a source of income, but also have an important role in the redistribution of wealth and economic regulation, which aims to create overall welfare for society. This research aims to find out and empirically prove the influence of company size, environmental social governance and leverage on tax avoidance. The independent variables in this research are company size, environmental social governance, and leverage, while the dependent variable is tax avoidance. Determining the sample in this study used a purposive sampling method, based on this method, 7 companies were obtained with research for 5 years, so that 35 samples of observation data were obtained. The data used in this research is secondary data using several annual financial reports on Kompas 100 indexed companies listed on the Indonesia Stock Exchange for 2019-2023. The data analysis used is multiple linear regression analysis with processing and using Eviews 12SV software. The results of this research show that partially company size has an effect on Tax Avoidance, Environmental Social Governance has no effect on Tax Avoidance and Leverage has an effect on Tax Avoidance. Simultaneously, company size, environmental social governance and leverage together influence tax avoidance